Inorganic nanomaterials in polymeric ultrafiltration membranes for water treatment - Goh, Pei Sean (Taylor and Francis Inc., 2015)
Due to the rapid expansion of nanotechnology and the increasing range of nanomaterials under production and development, a significant amount of research interest has been dedicated to the innovative exploitations of various inorganic nanomaterials in environmental applications. The incorporation of inorganic nanomaterials as fillers within a polymeric matrix has expanded opportunities to produce a multifunctional nanocomposite membrane that is capable of performing tasks beyond separation alone. The architectures and performances of these nanocomposite membranes have triumphed over polymeric membranes to overcome the underlying conspicuous drawbacks. This review aims to shed more light on the roles of inorganic nanomaterials in advancing the characteristics and separation performance of polymeric ultrafiltration membranes. Inorganic nanofillers such as metal oxides, metals and carbon-based materials are incorporated into polymeric membranes to render the desired properties for ultrafiltration separations. Novel strategies using a wide range of these inorganic nanomaterials have been well explored and established for the manufacturing of membrane with significantly enhanced properties that are highly desired to heighten the separation performances. With the renaissance of this emerging innovative technology, many possible solutions and valuable options can be offered to serve as the primary driver in excelling ultrafiltration membrane technology